Chemopreventive Potential of Dietary Nanonutraceuticals for Prostate Cancer: An Extensive Review - Chopra, Hitesh; Bibi, Shabana; Goyal, Rajat; Gautam, Rupesh K.; Trivedi, Rashmi; Upadhyay, Tarun Kumar; Mujahid, Mohd Hasan; Shah, Mohammad Ajmal; Haris, Muhammad; Khot, Kartik Bhairu; Gopan, Gopika; Singh, Inderbir; et al. (Frontiers in Oncology, 2022)
There are more than two hundred fifty different types of cancers, that are diagnosed around the world. Prostate cancer is one of the suspicious type of cancer spreading very fast around the world, it is reported that in 2018, 29430 patients died of prostate cancer in the United State of America (USA), and hence it is expected that one out of nine men diagnosed with this severe disease during their lives. Medical science has identified cancer at several stages and indicated genes mutations involved in the cancer cell progressions. Genetic implications have been studied extensively in cancer cell growth. So most efficacious drug for prostate cancer is highly required just like other severe diseases for men. So nutraceutical companies are playing major role to manage cancer disease by the recommendation of best natural products around the world, most of these natural products are isolated from plant and mushrooms because they contain several chemoprotective agents, which could reduce the chances of development of cancer and protect the cells for further progression. Some nutraceutical supplements might activate the cytotoxic chemotherapeutic effects by the mechanism of cell cycle arrest, cell differentiation procedures and changes in the redox states, but in other, it also elevate the levels of effectiveness of chemotherapeutic mechanism and in results, cancer cell becomes less reactive to chemotherapy. In this review, we have highlighted the prostate cancer and importance of nutraceuticals for the control and management of prostate cancer, and the significance of nutraceuticals to cancer patients during chemotherapy.